Microstructure and properties of in situ A356/TiB2 composite - 乐永康 陈东 马乃恒 张文静 毛健伟 王浩伟 (Transactions of Nonferrous Metals Society of China, 2006)
In situ A356/TiB2 composites were successfully fabricated via in-melt reaction among aluminium alloy, K2TiF6 and KBF4 compounds. The composite was examined by using XRD, SEM and EDX techniques. The experimental results reveal that TiB2 are dispersed homogeneously into the aluminium alloy matrix. The mechanical properties of the composites increase significantly with the addition of reinforcement, and the tensile fractography of the composite exhibits to be ductile though the elongation of the composites decreases compared with the unreinforced matrix alloy.